Comparison of postoperative analgesia with methadone versus morphine in cardiac surgery - Carvalho,Ana Carolina (2018)
Abstract Background and objectives: Pain is an aggravating factor of postoperative morbidity and mortality. The aim of this study was to compare the effects of methadone versus morphine using the numerical rating scale of pain and postoperative on-demand analgesia in patients undergoing myocardial revascularization. Method: A randomized, double-blind, parallel clinical trial was performed with patients undergoing coronary artery bypass grafting. The subjects were randomly divided into two groups: morphine group and methadone group. At the end of cardiac surgery, 0.1 mg.kg−1 adjusted body weight of methadone or morphine was administered intravenously. Patients were referred to the ICU, where the following was assessed: extubation time, time to first analgesic request, number of analgesic and antiemetic drug doses within 36 h, numerical pain scale at 12, 24, and 36 h postoperatively, and occurrence of adverse effects. Results: Each group comprised 50 patients. Methadone showed 22% higher efficacy than morphine as it yielded a number-needed-to-treat score of 6 and number-needed-to-harm score of 16. The methadone group showed a mean score of 1.9 ± 2.2 according to the numerical pain scale at 24 h after surgery, whereas as the morphine group showed a mean score of 2.9 ± 2.6 (p = 0.029). The methadone group required less morphine (29%) than the morphine group (43%) (p = 0.002). However, the time to first analgesic request in the postoperative period was 145.9 ± 178.5 min in the methadone group, and 269.4 ± 252.9 in the morphine group (p = 0.005). Conclusions: Methadone was effective for analgesia in patients undergoing coronary artery bypass grafting without extracorporeal circulation.